Kunstværket som kontraværdi – Asger Jorns kritik af Marx’ økonomistiske værditænkning i Kapitalen - Erslev Andersen, Jørn (Slagmark - Tidsskrift for idéhistorie, 2018)
THE WORK OF ART AS COUNTER-VALUE: ASGER JORN'S CRITIQUE OF MARX'S ECONOMISK VALUE-THINKING IN CAPITAL As one of the rather significant and influential Modernist and Avant-garde artists of the 20th century Asger Jorn is internationally well-known and admired. Lesser known – or lesser accepted in the reception of his work – is the fact that his many critical writings on art, philosophy, and politics as well as his archives and political activism are integrated and important parts of his entire artwork. For the first time in the reception of Jorn’s critical thinking the essay examines his Situationist criticism of Marx’ concepts of value, as outlined in the commodity analysis in Capital vol. 1, by regarding it a crucial example of his understanding of counter value as the only or most prominent quality of the artwork as such.